"Investigation of weight reduction and atherogenic features in response to aquafit among sedentary, obese middle-aged males". (June 2020) - Rezaeipour, Mohammadreza
Abstract: Aims: The potential interactive impacts of bodily exercise and the cholesteryl ester transfer protein (CETP) with the atherogenic lipid profile are controversial. This quasi-experimental study was designed to assess the effects of Aquafit patterns (continuous and intermittent) without a dietary intervention on weight reduction and features of the atherogenic lipid profile in sedentary obese middle-aged males. Methods: The study included sixty-eight obese middle-aged men with sedentary lifestyles who had reached out to the Helal Sports Complex of Ferdos for weight loss counselling (March to May 2018). They randomly assigned into two Aquafit training patterns: continuous Aquafit training with moderate-intensity (CAM) and intermittent Aquafit training with high-intensity (IAH). Both patterns lasted three months and consisted of three weekly sessions of 60-min each. The Wilcoxon Nonparametric Test was used to compare groups and times. Results: Comparison of monitored variables in the initial and final stages of the study showed no significant difference within and between groups, except significant reductions of body weight (0.5 kg, P = 0.03) and BMI (0.04 kg/m 2, P = 0.04) in the CAM group. Conclusions: In the absence of dietary intervention, the features of the atherogenic lipid profile in both Aquafit training patterns did not significantly improve. In the CAM group, obese middle-aged men with sedentary lifestyles had a modest but significant effect on weight reduction. Highlights: Water exercises do not have a significant impact on the atherogenic features in the absence of dietary intervention. Continuous Aquafit training with moderate intensity have a modest but significant impact on weight loss.